Biochar combined with nitrogen fertilizer: a practical approach for increasing the biomass digestibility and yield of rice and promoting food and energy security. (11th January 2022) - Ali, Izhar; Adnan, Muhammad; Ullah, Saif; Zhao, Quan; Iqbal, Anas; He, Liang; Cheng, FangWei; Muhammad, Ihsan; Ahmad, Shakeel; Wei, Shangqin; Jiang, Ligeng
Abstract: Rice is an important food crop that provides abundant biomass residues for biofuels. The use of nitrogen (N) fertilizer to increase rice biomass and yield in China has become increasingly common; however, the overuse of N fertilizer can create several environmental hazards and contribute to climate change. Biochar is well known for its ability to reduce N fertilizer amendment requirements without compromising rice yield and biomass. No studies to date have examined the effect of biochar on rice straw cellulose, pentose, and total sugar content under pretreatment and enzymatic hydrolysis. We conducted a two‐season – early (spring) and late (autumn) – field experiment that involved the application of four levels of biochar (0, 10, 20, and 30 t ha −1 ) and two levels of N (low: 135 kg ha −1 ; high: 180 kg ha −1 ) to evaluate rice biomass digestibility, yield, and soil quality during 2019. Compared with sole N fertilizer (i.e., both treatments with 0 t biochar ha −1 ), biochar application at the rate of 30 t ha −1 combined with 135 kg N ha −1 significantly ( P < 0.05) enhanced soil physiochemical properties, including increases in the activity of urease, catalase, and β ‐glucosidase by 69%, 25%, and 54%, respectively during both seasons (spring and autumn). Similarly soil microbial biomass carbon and nitrogen were increased in 30 t B ha −1 along with both N rates as compared to sole N treatments. Furthermore, hexoses, pentoses, and total sugars released with NaOH pretreatment were increased by 22%, 10%, and 12.93%, respectively, with 30 t biochar ha −1 plus 135 kg N ha −1 compared with the sole N treatments in both seasons. Moreover, under enzymatic hydrolysis, the hexoses, pentoses, and total sugars released were increased by 36%, 43%, and 39%, respectively, during both seasons. Grain yield, dry matter accumulation, and N production were 28%, 24%, and 19% higher, respectively, with 20 t biochar ha −1 combined with both 135 and 180 kg N ha −1 as compared with sole N applied treatments. There were no significant differences in the yield and biomass digestibility for biochar applied at rates of 20 and 30 t ha −1 along with N rates. Thus, biochar application at 30 t ha −1 with 135 kg N ha −1 was optimal for enhancing the soil fertility, biomass digestibility, and grain yield of rice. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd